Sequencing-based analysis for the identification of bacteria associated with severe early childhood caries (SECC) - Zainuddin, Zarina; Paiman, Abdul Qahhar; Dewi Ardini, Yunita (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Severe early childhood caries (SECC) is a microbialinfection that severely compromises the dentition ofyoung children.The aim of this study is toidentify bacteria associated with SECC and compare bacterial species between SECC and caries-free children. Bacterial samples were isolated from dental plaque samples of 3 to 6-yearold preschool children and the status of dental caries at the surface level was evaluated using World Health Organization (WHO) diagnostic criteria for decayed, missing and filled tooth surfaces (DFMS). 30 samples from the interproximal part were collected and genomic DNA was extracted using MasterPure™ Gram Positive DNA Purification Kit. Polymerase Reaction (PCR) was conducted on the genomic DNA extracted to amplify 16S rRNA gene and successfully amplified 16S rRNA gene from the samples was sent for sequencing.This research was approved by the IIUM Research Ethic Committee (IREC). Using the selected kit, genomic DNA was successfully extracted and PCR amplification of the bacterial 16S rRNAgeneusing universal bacterial primers was achieved giving a product of 1500 bp. Results from sequencing when analysedusing BLAST from the NCBI website, identified bacteria from the genus Vibrio, Haemophilus and Aggregatibacter from SECC samples while for caries-free samples Granulicatella was identified.